2022
DOI: 10.3311/ppch.19805
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Narrow Pores, Pore Size Distribution and Structural Details in Asymmetric Nanofiltration Membranes via Polyvinyl-pyrrolidone Additive

Abstract: The roles of polyvinyl-pyrrolidone (PVP) additive in the tailoring of pores, pore size distribution, morphologies and molecular weight cut-off (MWCO) in phase inversion asymmetric nanofiltration membranes was addressed. Using established solute transport method, scanning electron microscopy (SEM) and Minitab software, details analysis of the enhanced performance-properties of narrow pores nanofiltration membranes were verified. Experimental and analysis data revealed that the membranes prepared with 2 wt% of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…It was revealed that at higher polymer concentration the narrower pore size distribution was produced. Hence, high polymer concentration (> 20 wt%) not only improved the membranes performances but also produced good membranes characteristics as well as the narrowest pore size distribution as reported by other researchers [9,18,32].…”
Section: Morphologies and Pore Size Distributionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was revealed that at higher polymer concentration the narrower pore size distribution was produced. Hence, high polymer concentration (> 20 wt%) not only improved the membranes performances but also produced good membranes characteristics as well as the narrowest pore size distribution as reported by other researchers [9,18,32].…”
Section: Morphologies and Pore Size Distributionsupporting
confidence: 64%
“…A skinned, thin and dense asymmetric nanofiltartion (NF) membrane could be prepared by using dry/wet phase inversion technique [4,5]. In this technique, the formation of fine skinned membranes depends on two major factors of kinetic and thermodynamic factors which including of interactions between solvents and polymers, interactions between sol-vents and non-solvents, interfacial stability, solvent de-mixing rate [6][7][8][9]. Polymers like polyvinylidene fluoride (PVDF), cellulose acetate (CA), polysulfone (PSf), polyethersulfone (PES) have been used for the making asymmetric membranes due to their good thermal stability, outstanding oxidative and good mechanical strength [10,11].…”
Section: Introductionmentioning
confidence: 99%